Incremental Value of a Futures Hedge Using Realized Ranges. Issue 7 (21st March 2013) - Sheu, Her‐Jiun; Lai, Yu‐Sheng
Abstract This study investigates the information content of realized ranges for futures hedging. Hedge ratio estimation using generalized autoregressive conditional heteroscedasticity (GARCH) models augmented with intraday price range is proposed. Empirical investigations using the S&P 500 equity index data show that the in‐sample fitting of spot–futures distribution is improved by the information recovered from intraday price ranges. Furthermore, the out‐of‐sample forecasting results show that both the statistical and economic hedging effectiveness increase with the inclusion of intraday price ranges along with intraday and daily price returns. Results indicate that informative realized ranges are valuable for futures hedging. © 2013 Wiley Periodicals, Inc. Jrl Fut Mark 34:676–689, 2014